'Beyond international human rights law – music and song in contextualised struggles for gender equality'. (2nd January 2022) - Ghadery, Farnush
ABSTRACT: While human rights law remains the foremost tool for the advancement of women's rights, particularly in the eyes of lawyers and legal scholars, this article highlights other approaches in the struggle for gender equality worthy of attention. Elsewhere this author has argued that the hegemony of Western thought in feminist theory and human rights law has inhibited the recognition that across the globe a variety of different epistemologies, discourses, and approaches are being used for advancing gender equality. This article builds on this claim by drawing attention to the role of music and song as part of contextualised feminist resistance efforts, both by social movements and artists/artistic collectives. The outlined examples revert to music both as a form of resistance to dominant patriarchal structures and a form of advocacy to change those inequalities. As such, this article attempts to connect the scholarship on transnational legal feminism with that of music.